2015
DOI: 10.15171/ijhpm.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

"Hearing from all sides" How legislative testimony influences state level policy-makers in the United States

Abstract: Background: This paper investigates whether state legislators find testimony influential, to what extent testimony influences policy-makers' decisions, and defines the features of testimony important in affecting policy-makers' decisions. Methods: We used a mixed method approach to analyze responses from 862 state-level legislators in the United States (U.S.). Data were collected via a phone survey from January-October, 2012. Qualitative data were analyzed using a general inductive approach and codes were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…A qualitative study with nutrition and obesity researchers active in policy dissemination found that cultivating relationships with policymakers, use of intermediaries (eg, professional associations or nonprofit organizations that aim to improve knowledge sharing between producers and users of knowledge) in this work, and providing relevant policy communication training to researchers are promising strategies for success in knowledge translation into policy (20). Moreland-Russell et al qualitatively examined how legislative testimony influences the actions of legislators in our study and found that it influences awareness of issues and legislative decision-making and that presenter credibility, knowledge, and expertise increase the influence of testimonies (17). …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A qualitative study with nutrition and obesity researchers active in policy dissemination found that cultivating relationships with policymakers, use of intermediaries (eg, professional associations or nonprofit organizations that aim to improve knowledge sharing between producers and users of knowledge) in this work, and providing relevant policy communication training to researchers are promising strategies for success in knowledge translation into policy (20). Moreland-Russell et al qualitatively examined how legislative testimony influences the actions of legislators in our study and found that it influences awareness of issues and legislative decision-making and that presenter credibility, knowledge, and expertise increase the influence of testimonies (17). …”
Section: Discussionmentioning
confidence: 76%
“…We adapted questions from a previously developed measure validated with state legislators and cognitively tested with representatives of the advocate sample (8,1517). To measure information seeking and use, we asked participants to rank a series of statements on a 5-point scale (1 = never, 5 = always) on the basis of how often they used each source of information when working on policy issues.…”
Section: Methodsmentioning
confidence: 99%
“…We measured legislators’ use of research evidence with an instrument that has been validated with state legislators (16, 4041). Details about the sources of instrument items and reliability coefficients are described elsewhere (16).…”
Section: Methodsmentioning
confidence: 99%
“…This may involve knowing the characteristics of the target audience and expressing data in meaningful ways (so-called “social math”[48]) [49]. The use of infographics to present data in accessible and appealing formats can also be a useful tool for more effectively packaging policy-relevant information [50,35]. …”
Section: Discussionmentioning
confidence: 99%
“…The core survey items were originally developed by Bogenschieder and Coorbett [31], with additional testing among state-level policymakers [34,35]. …”
Section: Methodsmentioning
confidence: 99%